Integrating Islamic Values in Higher Education: Challenges and Strategies for Moral Transformation in a Secularized Era - Belva Wihita Christianto; Akmal Noor Ridzqi; Sumarta (Lentera Peradaban: Journal on Islamic Studies, 2026)
This research aims to examine in depth the relationship between campus culture and the moral transformation of Muslim students, using Pelita Bangsa University Bekasi as a case study. The research is motivated by the increasing phenomenon of moral degradation among students in the digital era, such as unethical behavior on social media, academic dishonesty, and the weakening internalization of religious values due to globalization and secularization. This condition underscores the urgent role of higher education institutions not only as centers for knowledge transfer but also as strategic spaces for character and moral formation. This study employs a qualitative approach with a descriptive-analytical design, combining library research and a limited case study. Informants were selected purposively, involving Muslim students across various semesters and those active in Islamic student organizations to comprehensively understand the dynamics of moral transformation. The findings indicate that campus culture plays a significant role in internalizing Islamic values such as honesty, responsibility, discipline, and tolerance. However, challenges arise from student subculture resistance, the influence of a permissive digital culture, and the weak implementation of campus ethical policies. While Islamic Religious Education (PAI) courses can foster more reflective moral changes, they have not yet fully addressed the structural moral crisis. This research emphasizes the importance of integrating moral values into the curriculum, implementing a "hidden curriculum," and strengthening digital literacy and moral mentoring. In conclusion, student moral transformation requires a collaborative and sustainable approach to produce graduates with integrity and social responsibility.